If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 = -4x + -35 Reorder the terms: 1 + 2x = -4x + -35 Reorder the terms: 1 + 2x = -35 + -4x Solving 1 + 2x = -35 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 1 + 2x + 4x = -35 + -4x + 4x Combine like terms: 2x + 4x = 6x 1 + 6x = -35 + -4x + 4x Combine like terms: -4x + 4x = 0 1 + 6x = -35 + 0 1 + 6x = -35 Add '-1' to each side of the equation. 1 + -1 + 6x = -35 + -1 Combine like terms: 1 + -1 = 0 0 + 6x = -35 + -1 6x = -35 + -1 Combine like terms: -35 + -1 = -36 6x = -36 Divide each side by '6'. x = -6 Simplifying x = -6
| 10*x=15*y | | x^2+8x+16=5 | | 2x-10+3x=15 | | 3x-4x=8 | | 217-2x=43x+17 | | 2(4b+11)=5(b-4) | | 9x+9=3x+45 | | 3x^2-6x-8=0 | | 8-9x=88-44x | | 4+4x+4x=44 | | 8(w-1)=16(w+1) | | 8x=5-(x-13) | | -9(r-9)=-7(r+5) | | -4x+10+5x=14 | | -x-6+4x=9 | | 109-2x=6x+13 | | 6(h-2)=15h+6 | | 9=-x+3x+3 | | a-4a=2a+2-5a | | 7x-4+x=-76 | | 73-5x=4x+24 | | q-8=10 | | -10-5x=10-9x | | 7-8x=64-29x | | 5+7x=68 | | -11+t=-13 | | -13-8x=9x+21 | | 5x+9=-1 | | -4+w=5 | | 7x+4-x=40 | | 6x+12=-27-7x | | 7-2x=-13 |